The Influence of Green Organizational Culture, Green Employability, and Green Innovation on Employee Performance through Job Satisfaction at PT Geo Dipa Energi (Persero) - Retno Andriyana; Irma Setyawati (Jurnal Manajemen Bisnis, 2025)
The research highlights the importance of adopting environmental sustainability principles to enhance employee performance in the geothermal energy sector. Data were collected through questionnaires distributed to employees of PT Geo Dipa Energi (Persero). Using Partial Least Squares (PLS), the study tested hypotheses and analyzed both direct and indirect relationships among the variables. The findings show that green organizational culture significantly and positively affects both job satisfaction and employee performance. Green innovation also has a significant positive effect on both outcomes. Although green employability does not significantly influence job satisfaction, it has a positive and significant impact on employee performance. Job satisfaction is found to mediate the relationship between green organizational culture and employee performance positively. The study suggests that PT Geo Dipa Energi (Persero) should continue to strengthen its green organizational culture and innovation while also developing training programs to enhance green employability. These efforts are expected to improve both employee satisfaction and performance, offering practical insights into the role of sustainability initiatives in organizational development.